2023
DOI: 10.3390/ijms24065135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenotype and Genotype Virulence and Antimicrobial Factors of Salmonella Typhimurium Isolated from Human Milk

Abstract: Salmonella is a common foodborne infection. Many serovars belonging to Salmonella enterica subsp. enterica are present in the gut of various animal species. They can cause infection in human infants via breast milk or cross-contamination with powdered milk. In the present study, Salmonella BO was isolated from human milk in accordance with ISO 6579-1:2017 standards and sequenced using whole-genome sequencing (WGS), followed by serosequencing and genotyping. The results also allowed its pathogenicity to be pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The functions of SPIs have been mainly studied in gastrointestinal pathogenic bacteria, such as S. typhimurium and S. enteritidis , that have a wide range of hosts and cause self-limited diarrhea in humans and animals ( 7 , 9 , 25 ). SPIs have important effects on the bacterial physiology and interactions with the environment and gastrointestinal tract of mammals ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of SPIs have been mainly studied in gastrointestinal pathogenic bacteria, such as S. typhimurium and S. enteritidis , that have a wide range of hosts and cause self-limited diarrhea in humans and animals ( 7 , 9 , 25 ). SPIs have important effects on the bacterial physiology and interactions with the environment and gastrointestinal tract of mammals ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LoiA can also regulate multiple virulence-related genes in S. typhimurium through the negative regulation of Lon protease ( 29 ). Recent studies have demonstrated that S. enteritidis and S. typhimurium may share the same virulence mechanisms for epithelial cell invasion and survival within macrophages ( 9 , 25 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…as containing unique sequences to the genus Salmonella. In addition, SifA gene, located in chromosome, decrease of kinesin accumulation in the SCV, modulation of vesicular trafficking, SCV perinuclear migration, SCV membrane integrity and SipA, located in SPI-1, Actin Stabilization and localization of actin filaments during invasion, stabilization of VAP, correct localization of SifA and PipB2, SCV perinuclear migration and morphology (Shalal et al, 2023;Maaroof and Dhayea, 2023;Pławińska-Czarnak et al, 2023;Yuliangsih et al, 2019).…”
Section: Introductionmentioning
confidence: 99%